Wiara a intencja małżeństwa – ich wzajemna relacja na płaszczyźnie kanoniczno-teologicznej - Czujek, Marcin (Ius Matrimoniale, 2016)
The issue of the mutual relation of faith and intentions of marriage is the subject of discussion and inquiry canonical and theological. The intensity of reflections and questions on this topic is clearly connected with the change in the level of religious societies, the perception of moral and doctrinal issues and sometimes also with the expectations of the Church. A credible answer to every issue must take into account every aspect, but first must consider the truth about the man which is able to find and know God. With this assumption comes also the position of canon law doctrine proclaimed That the reality of the sacrifice of self and acceptance of the other person, even when there is no faith turns out to be more difficult to Achieve but not impossible to make. Whereas studying the dynamics of development of an act of faith in a man can better assess the same intention to marry.